Multiscale modelling of fluid-immersed granular media - Clément, Christian Paul André René (2010)
In this thesis we present numerical simulation studies of fluid-immersed granular systems using models of varying scales and complexities. These techniques are used to examine the effects of an interstitial fluid on the dynamics of dense granular beds within a number of vibrated systems.